Platform-Capital's 'App-etite' for Control: A Labour Process Analysis of Food-Delivery Work in Australia. (June 2020) - Veen, Alex; Barratt, Tom; Goods, Caleb
This qualitative case study adopts a labour process analysis to unpack the distinctive features of capital's control regimes in the food-delivery segment of the Australian platform-economy and assesses labour agency in response to these. Drawing upon worker experiences with the Deliveroo and UberEATS platforms, it is shown how the labour process controls are multi-facetted and more than algorithmic management, with three distinct features standing out: the panoptic disposition of the technological infrastructure, the use of information asymmetries to constrain worker choice, and the obfuscated nature of their performance management systems. Combined with the workers' precarious labour market positions and the Australian political-economic context, only limited, mainly individual, expressions of agency were found.